The Effect of Blanching Time and Amount of Sugar on Quality of Chinese Mustard Wet Candy - Erin Alawiyah Siregar; Herla Rusmarilin; Lasma Nora Limbong (Universitas Sumatera Utara, 2015)
The purpose of this study was to determine the effect of blanching time and amount of sugaron the quality and sensory test of candied Chinese mustard. This study was conducted in July to September 2013 in Food Technology Laboratory, Agriculture Faculty, North Sumatera University, Medan. This study was using completelyrandomized design with two factors, i.e blanching time (L) (2, 3, 4, and 5 minutes) and amount of sugar (P) (55, 60, 65, and 70 g). The analyzed parameters were moisture content (%), vitamin C content (mg/100 g sample),total soluble solid (oBrix), crude fiber content (%), and sensory test (color, flavor, taste, and texture). The results showed that blanching time per 100 ml of soaking water had a highly significanteffect on moisture content (%), vitamin C content (mg/100 g sample), total soluble solid (oBrix), crude fiber content (%), sensory test (color and flavor); had a significant effect on texture and had no effect on taste. The amount ofsugar had a highly significant effect on moisture content (%), vitamin C content (mg/100 g sample), total soluble solid (oBrix), sensory test (taste, flavor, and texture), and had no significant effect on crude fiber content (%) andorganolepticvalue of colour. The interaction of blanching time and amount of sugar had a highly significant effect on vitamin C content (mg/100 g sample). The best treatment which gave the best effect on Chinese mustard wet candy was 3 minutes of blanching time and amount of sugar 65 g. Keyword : Blanching time, amount of sugar, wet candy, chinese mustard.